2017
DOI: 10.1292/jvms.16-0475
|View full text |Cite
|
Sign up to set email alerts
|

Na<sup>+</sup>/Ca<sup>2+</sup> exchanger contributes to stool transport in mice with experimental diarrhea

Abstract: The Na+/Ca2+ exchanger (NCX) is a bidirectional transporter that is controlled by membrane potential and transmembrane gradients of Na+ and Ca2+. To reveal the functional role of NCX on gastrointestinal motility, we have previously used NCX1 and NCX2 heterozygote knockout mice (HET). We found that NCX1 and NCX2 play important roles in the motility of the gastric fundus, ileum and distal colon. Therefore, we believed that NCX1 and NCX2 play an important role in transport of intestinal contents. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…digestive system [1,13], and immune system [4,5]. Diarrhea and constipation are two of the most typical symptoms that appear with stress, and the colon is involved in these [10].…”
mentioning
confidence: 99%
“…digestive system [1,13], and immune system [4,5]. Diarrhea and constipation are two of the most typical symptoms that appear with stress, and the colon is involved in these [10].…”
mentioning
confidence: 99%
“…Although NCX1 and NCX2 were found to be expressed in the myenteric nerve plexus of the proximal colon and the colon transversum as well as longitudinal and annular muscular layers, the function of NCX1 and NCX2 in intermuscular neurons may be different from that in smooth muscle[74]. Kazuhiro et al have found that in a diarrhea model induced with magnesium sulfate or 5-HT, the diarrhea in NCX2 heterozygous knockout mice (NCX2 HET) was more serious than that in wild-type mice (WT), but the diarrhea in NCX1 heterozygous knockout mice (NCX1 HET) showed no significant changes from that of WT[75]. Magnesium sulfate-induced diarrhea was exacerbated in NCX2 HET by decreasing normal and soft fecal materials and increasing watery fecal materials, however, PGE2-induced diarrhea in NCX1 HET and NCX2 HET was similar to that in the WT[75].…”
Section: Ncx1 and The Intestinementioning
confidence: 99%
“…Kazuhiro et al have found that in a diarrhea model induced with magnesium sulfate or 5-HT, the diarrhea in NCX2 heterozygous knockout mice (NCX2 HET) was more serious than that in wild-type mice (WT), but the diarrhea in NCX1 heterozygous knockout mice (NCX1 HET) showed no significant changes from that of WT[75]. Magnesium sulfate-induced diarrhea was exacerbated in NCX2 HET by decreasing normal and soft fecal materials and increasing watery fecal materials, however, PGE2-induced diarrhea in NCX1 HET and NCX2 HET was similar to that in the WT[75]. The researchers believe that this finding may be due to the mechanism of 5-HT-induced diarrhea involving stimulation of the 5-HT3 receptor in myenteric plexus neurons and its downstream cholinergic and tachykinin excitatory pathways[76,77].…”
Section: Ncx1 and The Intestinementioning
confidence: 99%
“…The stress response of the autonomic nervous system and endocrine system is indispensable for the maintenance of life, but when that stress becomes long-term or chronic, stress response can cause disability in social life. There are serious effects caused by stress, such as gastrointestinal disorders [ 32 ], depression [ 9 ], eating disorders [ 3 ], immunological disease [ 7 , 8 ], neurodegenerative disease [ 18 , 47 , 48 ], and cardiovascular diseases [ 11 ]. We now focus on the relationship between stress and gastrointestinal motility disorders among serious effects listed above.…”
mentioning
confidence: 99%